2019
DOI: 10.3892/ol.2019.10698
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key pathways and genes in colorectal cancer to predict the prognosis based on mRNA interaction network

Abstract: The aim of the present study was to identify key genes in colorectal cancer (CRC) that could be used to reliably diagnose this disease and to explore the potential underlying mechanisms in silico. The gene expression profiles of primary human cancer datasets GSE21510 and GSE32323 were downloaded from the Gene Expression Omnibus database. The limma R software package was used to identify differentially expressed (DE) genes. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Red ( * ) = high expression correlates with better overall survival. Green ( * ) = low expression correlates with better overall survival [ 28 , 66 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Red ( * ) = high expression correlates with better overall survival. Green ( * ) = low expression correlates with better overall survival [ 28 , 66 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the future, combination treatments to limit these effects should be further investigated. [28,[66][67][68][69][70]. www.oncotarget.com BTG2 was identified as a top gene upregulated by all four drugs (5-FU, CPT-11, oxaliplatin, and cisplatin).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that p21, together with p53, is involved in cell cycle arrest when down-regulated in tumor tissue ( Normand et al., 2005 ; Zhu et al., 2019 ). FOXO1 and FOXO3 are involved in inducing apoptosis and both have been found to be related to Non-small cell lung cancer progression when down-regulated ( Gao et al., 2018 ; Meng et al., 2010 ; Mikse et al., 2010 ; Shi et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The repurposing of existing drugs for certain diseases could reduce the time and cost compared to de novo drug development. By this time, several authors have suggested different sets of key genes (KGs) to explore molecular mechanisms and pathogenetic processes of CRC progression [ 14 45 ] in which some studies have employed multiple datasets to identify CRC-causing KGs [ 15 17 , 22 , 25 , 26 , 31 , 32 , 37 , 40 43 , 46 49 ]. Few studies also explored their suggested KGs-guided candidate drug molecules for the treatment against CRC [ 14 , 37 , 40 42 , 50 59 ].…”
Section: Introductionmentioning
confidence: 99%